PENGARUH PENJUALAN, BIAYA OPERASI, DAN RETURN SAHAM TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Devi Satria Putri (AKUNTABILITAS, 2015)
This study aims to provide empirical evidence of the influence of sales, operating expenses, and stock returns manufacturing company in Indonesia Stock Exchange in 2009-2013 in the long run. Sales diiukur the natural log total sales, operating costs measured by the natural log of operational costs, the stock return is measured by the natural log stock return, while CSR is measured by a score of disclosure GRI G4. The sample used by 25 firms reporting CSR activities in the annual report of the company. The study concluded that sales, operating costs and stock returns have no significant effect on corporate social responsibility. This is due to the implementation of CSR in Indonesia mandotori so the motivation of these companies do CSR is to be able to avoid the company of a conflict with the public and the government, instead of focusing on product innovation and quality improvement, as well as care for the maintenance of the environment, economy, and energy conversion .